A revision of the genus Pulaeus Den Heyer, with descriptions of a new genus and four new Brazilian species (Acari: Prostigmata: Cunaxidae) - de Castro, Tatiane Marie Martins Gomes; Heyer, Jacob Den (Zootaxa, 2009)
A new genus, Lupaeus gen. nov., is created to contain part of the described species in the genus Pulaeus Den Heyer. A key to the genera of the tribe Pulaeini, to which these two genera belong, and one auxiliary key to the species of Brazil and South Africa, are provided. Four new species, viz. Pulaeus myrtaceus sp. nov., P. quadrisolenidius sp. nov., Lupaeus lectus sp. nov. and L. lobidorsalis sp. nov. are described and figured. P. martini Den Heyer, 1981 is designated as type species for the new genus. New nomenclatural combinations are reported.